إستقلال وسيادة الدول وحقها في التمثيل الدبلوماسي : دراسة ‏حول التمثيل الدبلوماسي لليبيا اثناء ثورة فبراير 2011‏ - درويش، عبد السلام (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This study aimed to critically analyse the concept of sovereignty and the right of diplomatic representation. The concept of sovereignty and the right of diplomatic representation are not new issues, as they have been discussed and dealt with in more than one study. All the findings show that the issue is the most important activity in international relations. It is subject to many criteria, most importantly international law and the interests of the participating countries. To build and maintain close relations with neighbouring countries and to integrate into the international community, and furthermore the ability to defend the interests of the State and achieve its interests by building balanced relations and clarifying the role of diplomatic missions in and abroad, and this diplomatic mission should not be used in any manner to defend repressive regimes and Tyranny. An example of this can be seen in the era of former dictator Colonel Gaddafi's regime, who employed all his leadership power to capture diplomatic freedom and repress freedom of expression in Libya. As he attempted to create advantages to some countries in order for him to continue with his dictatorship policies. By doing so, he was able to strengthen his control over his opponents and suppress liberties in Libya. The Post Gaddafi scenario raises serious questions about Libya's future prospects, whether among its political actors or with the international community. The conflict of Western interests in Libya will continue to contribute to prolonging wars between the Libyan major parties, which in return can influence these major policies to a great extent. The foreign policy should be subject to the requirements of the contemporary international society and keep pace with its changes. It is the constitution of the State that determines the bodies or organs authorized to missions abroad. In any case, the envoy does not represent the person or device he sent, but instead should represent the sending State's sovereignty and implements its foreign policies